Genome-wide investigation and transcriptional analysis of cytosine-5 DNA methyltransferase and DNA demethylase gene families in tea plant (Camellia sinensis) under abiotic stress and withering processing - Zhu, Chen; Zhang, Shuting; Zhou, Chengzhe; Chen, Lan; Fu, Haifeng; Li, Xiaozhen; Lin, Yuling; Lai, Zhongxiong; Guo, Yuqiong (PeerJ, 2020)
DNA methylation is a highly conserved epigenetic modification involved in many biological processes, including growth and development, stress response, and secondary metabolism. In the plant kingdom, cytosine-5 DNA methyltransferase (C5-MTase) and DNA demethylase (dMTase) genes have been identified in some plant species. However, to the best of our knowledge, no investigator has focused on the identification and analysis of C5-MTase and dMTase genes in tea plants (Camellia sinensis) based on genome-wide levels. In this study, eight CsC5-MTases and four dMTases were identified in tea plants. These CsC5-MTase genes were divided into four subfamilies, including CsMET, CsCMT, CsDRM and CsDNMT2. The CsdMTase genes can be classified into CsROS, CsDME and CsDML. Based on conserved domain analysis of these genes, the gene loss and duplication events occurred during the evolution of CsC5-MTase and CsdMTase. Furthermore, multiple cis-acting elements were observed in the CsC5-MTase and CsdMTase, including light responsiveness, phytohormone responsiveness, stress responsiveness, and plant growth and development-related elements. Then, we investigated the transcript abundance of CsC5-MTase and CsdMTase under abiotic stress (cold and drought) and withering processing (white tea and oolong tea). Notably, most CsC5-MTases, except for CsCMT1 and CsCMT2, were significantly downregulated under abiotic stress, while the transcript abundance of all four CsdMTase genes was significantly induced. Similarly, the same transcript abundance of CsC5-MTase and CsdMTase was found during withering processing of white tea and oolong tea, respectively. In total, our findings will provide a basis for the roles of CsC5-MTase and CsdMTase in response to abiotic stress and the potential functions of these two gene families in affecting tea flavor during tea withering processing.
Keywords: Camellia sinensis; C5-MTase; dMTase; Stress response; Withering processing; Transcript abundance